Effectiveness of the FIFA11+ Referees Injury Prevention Program in improving athletic performance in male professional soccer referees - Palermi, S.; Vecchiato, M.; Spinelli, A.; Gallinoro, C. M.; Annarumma, G.; Di Gegorio, A.; Nuccio, F.; Di Salvatore, M.; Cozzolino, A.; Tuzi, M.; Sirico, F. (Medicina dello Sport, 2023)
BACKGROUND: Football refereeing requires physical and tactical skills that imply risks of injuries. The Fédération International de Football Association (FIFA) 11+ Referees Injury Prevention Program (FIFA11+ for Referees) is a complete warm-up package based on the specific injury profile of referees and on the "FIFA11+" injury prevention program for players. It consists of three parts: part 1 - running part; part 2 - plyometric and balance exercises; part 3 - high-speed and change-of-direction running. This study aimed to investigate if different components of the FIFA11+ for Referees program separately could positively affect the acute athletic performance of referees.